NPY and Gene Therapy for Epilepsy: How, When,... and Y - Cattaneo, Stefano; Verlengia, Gianluca; Marino, Pietro; Simonato, Michele; Bettegazzi, Barbara (Frontiers in Molecular Neuroscience, 2021)
Neuropeptide Y (NPY) is a neuropeptide abundantly expressed in the mammalian central and peripheral nervous system. NPY is a pleiotropic molecule, which influences cell proliferation, cardiovascular and metabolic function, pain and neuronal excitability. In the central nervous system, NPY acts as a neuromodulator, affecting pathways that range from cellular (excitability, neurogenesis) to circuit level (food intake, stress response, pain perception). NPY has a broad repertoire of receptor subtypes, each activating specific signaling pathways in different tissues and cellular sub-regions. In the context of epilepsy, NPY is thought to act as an endogenous anticonvulsant that performs its action through Y2 and Y5 receptors. In fact, its overexpression in the brain with the aid of viral vectors can suppress seizures in animal models of epilepsy. Therefore, NPY-based gene therapy may represent a novel approach for the treatment of epilepsy patients, particularly for pharmaco-resistant and genetic forms of the disease. Nonetheless, considering all the aforementioned aspects of NPY signaling, the study of possible NPY applications as a therapeutic molecule is not devoid of critical aspects. The present review will summarize data related to NPY biology, focusing on its anti-epileptic effects, with a critical appraisal of key elements that could be exploited to improve the already existing NPY-based gene therapy approaches for epilepsy.